2001
DOI: 10.1124/mol.59.5.960
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Direct Protein Kinase-C Mediated Modulation ofN-Methyl-d-aspartate Receptor Current

Abstract: Protein kinase-C (PKC) activation differentially affects currents from N-methyl-D-aspartate (NMDA) type glutamate receptors depending upon their subunit composition. Experiments using chimeras initially indicated that the cytoplasmic C-terminal tails of NR2B (responsive to PKC) and NR2C (unresponsive to PKC) subunits contain the amino acid residues responsible for the observed disparity of PKC effects. However, truncation and point mutation experiments have suggested that PKC action on NMDA receptors may be en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
157
1
11

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(174 citation statements)
references
References 37 publications
5
157
1
11
Order By: Relevance
“…This may be due to a difference in the subtypes of the NR2 subunit since it has been suggested that NR2A and/or NR2B work for LTP while NR2C and/or NR2D work for LTD (Hrabetova et al, 2000). If the effect of HGF on the NMDA receptor is mediated mainly by PKC, the selectivity for LTP is consistent with the selectivity of the PKC-induced phosphorylation of NR2A and NR2B, and not of NR2C and NR2D (Mori et al, 1993;Liao et al, 2001). In contrast to HGF, BDNF, which acts on a different but similar tyrosine-kinase type receptor to c-Met, attenuates LTD via PLC .…”
Section: Discussionmentioning
confidence: 50%
“…This may be due to a difference in the subtypes of the NR2 subunit since it has been suggested that NR2A and/or NR2B work for LTP while NR2C and/or NR2D work for LTD (Hrabetova et al, 2000). If the effect of HGF on the NMDA receptor is mediated mainly by PKC, the selectivity for LTP is consistent with the selectivity of the PKC-induced phosphorylation of NR2A and NR2B, and not of NR2C and NR2D (Mori et al, 1993;Liao et al, 2001). In contrast to HGF, BDNF, which acts on a different but similar tyrosine-kinase type receptor to c-Met, attenuates LTD via PLC .…”
Section: Discussionmentioning
confidence: 50%
“…PKC phosphorylates GluN2B subunit on serine residues (Ser 1303 or Ser 1323 ) located in its carboxylterminal domain (41), and each of these phosphorylations induces a potentiation of NMDA currents (41,42). To determine whether 5-HT 2A receptor activation elicits GluN2B phosphorylation, acute PFC slices from juvenile and adult animals were exposed to DOI and Ser 1303 phosphorylation state was analyzed in synaptosomal enriched fraction by Western blotting using a phospho-site specific antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Such properties include desensitization, peak current amplitude, and run-down. For example, tyrosine phosphorylation or phosphorylation by protein kinase A has been found to increase the desensitization rate of neuromuscular AChRs (56,57), and protein kinase C has been shown to phosphorylate serines 1303 and 1323 directly in the C terminus of the NR2B subunit, leading to an increase in peak current amplitude of the NMDA receptor (58). In addition, the phosphotyrosine state of the GABA receptor is controlled by a PTPase, which regulates the run-down of GABA-activated chloride currents (59).…”
Section: Discussionmentioning
confidence: 99%